Areal Density Measurement is a Convenient Method for the Determination of Porcine Islet Equivalents without Counting and Sizing Individual Islets - N. Lembert; J. Wesche; P. Petersen; M. Doser; H. D. Becker; H. P. T. Ammon (Cell Transplantation, 2003)
The determination of islet mass is important for the normalization of islet experiments in the laboratory and for the precise dosing of islets for transplantation. The common microscopical analysis is based on individual islet sizing, calculation of the frequency distribution, and conversion into islet equivalents (IEQ), which is the volume of a spherical islet with a diameter of 150 μm. However, islets are of irregular form, which makes this determination user dependent, and the analysis is irreproducible once the original sample is discarded. This routine technique of islet quantification was compared with the analysis of areal density measurements. It was assumed that the entire area occupied by islets can be expressed in IEQ without sizing and counting individual islets. Porcine islets were isolated by continuous digestion/filtration and purified by gradient centrifugation. Purified islets were stained with dithizone and were repeatedly pictured under the microscope with random area selection. A total of 51 pictures was taken from 11 different purifications and stained islets were detected by digital image analysis. The correlation coefficient (r) between both analyses was 0.977 with an underestimation of islet yield by areal density detection (slope: 0.75 ± 0.03). Areal density analysis per picture took about 1 min, which is about 10 times faster than the traditional method without increasing the method error (CV 2.1% vs. 2.7%). In summary, areal density measurements allow a rapid and reproducible estimation of IEQ without counting individual islets. It can be performed in a single step analysis without computer programming and is valuable for online determinations of islet yield preceding transplantation.